Tumor Microenvironment-Stimuli Responsive Nanoparticles for Anticancer Therapy - Thomas, Reju George; Surendran, Suchithra Poilil; Jeong, Yong Yeon (Frontiers in Molecular Biosciences, 2020)
Cancer is a disease that affects a large number of people all over the world. For treating cancer, nano-drug delivery system has been introduced recently with objective of increasing therapeutic efficiency of chemotherapeutic drug. The main characteristics of this system are the encapsulation of the insoluble chemotherapeutic cargo, increasing the period of circulation in the body, as well as the delivery of the drug at that specific site. Currently, the nano-drug delivery system based on the stimuli response is becoming more popular because of the extra features for controlling the drug release based on the internal atmosphere of cancer. This review provides a summary of different types of internal (pH, redox, enzyme, ROS, hypoxia) stimuli-responsive nanoparticle drug delivery systems as well as perspective for upcoming times.